The Impact of Online Learning During Covid-19 Pandemic on The Mental Health of Nursing Students - Prasetya Andhika Johan; Usman, Andi Mayasari; Widowati, Retno (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: The Covid-19 pandemic has had a significant impact on daily life. The Covid-19 pandemic affects learning activities directly into online learning, so students must adapt to new habits. Ineffective online learning has the potential to cause mental health disorders. Objective: This study aims to determine the impact of learning during the Covid-19 pandemic on students' mental health. Method: This research method uses a quantitative descriptive survey method with a cross sectional research design. A total of 66 people were selected by using accidental sampling. The research instrument used the Questionnaire Online Learning and the Self Reporting Questionnaire (SRQ)-20. Result: The result showed that Morethan half of the 49 respondents (74.2%) stated that online learning was not effective. And 35 respondents (53%) had no indication of mental disorders (Normal). Conclusion: In conclusion, there is no significant relationship between the impact of online learning and the mental health of students in the University of National nursing study program. Based on the results of the Chi-square statistical test output test with a 95% confidence level, it was obtained a P Value of (0.579) > ? value (0.05).